2018
DOI: 10.15837/ijccc.2018.1.2970
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of the PSO and GA for the m-MDPDPTW

Abstract: Abstract:The m-MDPDPTW is the multi-vehicles, multi-depots pick-up and delivery problem with time windows. It is an optimization vehicles routing problem which must meet requests for transport between suppliers and customers for the purpose of satisfying precedence, capacity and time constraints. This problem is a very important class of operational research, which is part of the category of NP-hard problems. Its resolution therefore requires the use of evolutionary algorithms such as Genetic Algorithms (GA) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
(16 reference statements)
0
5
0
Order By: Relevance
“…The authors use self-generated test instances and compare two GA variants with different methods, such as hill-climbing, in their evaluation. A GA for Multi-Depot PDPTW with homogeneous vehicles is presented in [22]. The GA uses a path representation, i.e., the order of the customers is stored in the genotype.…”
Section: Pickup and Delivery Problemsmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors use self-generated test instances and compare two GA variants with different methods, such as hill-climbing, in their evaluation. A GA for Multi-Depot PDPTW with homogeneous vehicles is presented in [22]. The GA uses a path representation, i.e., the order of the customers is stored in the genotype.…”
Section: Pickup and Delivery Problemsmentioning
confidence: 99%
“…Further, the service start time has to start within the specified time window [a i , b i ] of customer i (20). The time precedence relationship between pickup and delivery nodes is modeled using inequalities (21) through the service start at node i and i + n. Restrictions (22) ensure that the load L j is correctly updated after the customer i is visited. In addition, (23) guarantees that the capacity of the vehicle associated with the served customer i is not exceeded.…”
Section: Mathematical Model For the Multi-depot Pickup And Delivery P...mentioning
confidence: 99%
“…Tiwari et al [8] proved a modified environmental adaptation method can evade the incidence of being struck into local minima. Alaia et al [9] investigated a multi-vehicle, multidepot pickup and delivery problem with time windows and solved a benchmark example using a GA and PSO algorithm, and the results showed that the GA algorithm is better than the PSO algorithm. Jiang [10] used a dynamic clustering algorithm to solve the model that considered the order similarity and the picking time.…”
Section: State Of the Artmentioning
confidence: 99%
“…As the pickup point and delivery point presented a one-to-one corresponding relation in this study, first, the pickup points were randomly permutated and combined to form a chromosome during the coding process, the vehicles were inserted into multiple positions of the chromosome, and the delivery points were randomly inserted at each pickup point served by each vehicle. Taking five cargo owners and two vehicles as an example, first, a chromosome (2, 3, 5, 4, 1) was randomly generated, the vehicles were inserted into the chromosome to obtain (11,2,3,5,12,4,1), and the delivery points were inserted to acquire (11,2,3,7,8,5,10,12,4,9,1,6). Finally, the formed chromosome showed that the first vehicle provided the delivery service for cargo owners 2, 3, and 5, and the second vehicle provided the delivery service for cargo owners 1 and 4.…”
Section: Algorithm Design (1) Simulation Of Cargo Transport O2o Platform Distribution Design Via Anylogicmentioning
confidence: 99%
“…PSO begins from an initial swarm and utilizes cooperation to find the best solution where GA utilizes genetic operations. (Alaia et al, 2018) compared GA and PSO implementation in an optimization problem. They concluded that GA is the favourable approach although that it endures a few issues.…”
mentioning
confidence: 99%